Hybrid Living Materials: Digital Design and Fabrication of 3D Multimaterial Structures with Programmable Biohybrid Surfaces. (18th December 2019) - Smith, Rachel Soo Hoo; Bader, Christoph; Sharma, Sunanda; Kolb, Dominik; Tang, Tzu‐Chieh; Hosny, Ahmed; Moser, Felix; Weaver, James C.; Voigt, Christopher A.; Oxman, Neri
Abstract: Significant efforts exist to develop living/non‐living composite materials—known as biohybrids—that can support and control the functionality of biological agents. To enable the production of broadly applicable biohybrid materials, new tools are required to improve replicability, scalability, and control. Here, the Hybrid Living Material (HLM) fabrication platform is presented, which integrates computational design, additive manufacturing, and synthetic biology to achieve replicable fabrication and control of biohybrids. The approach involves modification of multimaterial 3D‐printer descriptions to control the distribution of chemical signals within printed objects, and subsequent addition of hydrogel to object surfaces to immobilize engineered Escherichia coli and facilitate material‐driven chemical signaling. As a result, the platform demonstrates predictable, repeatable spatial control of protein expression across the surfaces of 3D‐printed objects. Custom‐developed orthogonal signaling resins and gene circuits enable multiplexed expression patterns. The platform also demonstrates a computational model of interaction between digitally controlled material distribution and genetic regulatory responses across 3D surfaces, providing a digital tool for HLM design and validation. Thus, the HLM approach produces biohybrid materials of wearable‐scale, self‐supporting 3D structure, and programmable biological surfaces that are replicable and customizable, thereby unlocking paths to apply industrial modeling and fabrication methods toward the design of living materials. Abstract : Hybrid living materials (HLMs) are a class of multifunctional materials that harness the responsive capabilities of engineered bacteria in combination with established digital fabrication processes (e.g., computer‐aided design and additive manufacturing) for structural materials. The programmable biological control enabled by the multimaterial HLM framework creates new possibilities for large‐scale, structurally complex, and diversely functional hybrid living devices.